The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41598-019-44464-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of monosporidial and monoteliosporic cultures for unraveling the complexity of molecular pathogenesis of Tilletia indica pathogen of wheat

Abstract: Tilletia indica (Ti) - a quarantined fungal pathogen of wheat and its pathogenesis is chiefly governed by pathogen effectors secreted inside the host plant. The de novo genome sequencing of several field isolates and stages available could be used for understanding the molecular pathogenesis. The presence of gaps and low coverage of assembled genomes poses a problem in accurate functional annotation of such functions. In the present study attempts were made to improve the Ti d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In earlier studies, Gypsys were the most common repeat element, which was reported in T. indica and T. horrida (Wang et al, 2018;Gurjar et al, 2019;Mishra et al, 2019). In fungi, the Gypsy group is the most common type of TE (Gorinsek et al, 2004).…”
Section: Discussionmentioning
confidence: 92%
“…In earlier studies, Gypsys were the most common repeat element, which was reported in T. indica and T. horrida (Wang et al, 2018;Gurjar et al, 2019;Mishra et al, 2019). In fungi, the Gypsy group is the most common type of TE (Gorinsek et al, 2004).…”
Section: Discussionmentioning
confidence: 92%
“…The transposon types Gypsy followed by Copia , both belonging to the long terminal direct repeats (LTR) class of retrotransposons, were the most abundant in all three bunt species. Similarly, Gypsys were the most frequent TE reported in T. indica (Gurjar et al 2019 ; Mishra et al 2019 ) as well as in T. horrida (Wang et al 2018 ). Gypsy s are the most successful group of TEs in fungi (Gorinsek et al 2004 ) and plants (Sabot and Schulman 2006 ) and are capable to increase their number by autonomous transposition (Elliott and Gregory 2015 ).…”
Section: Discussionmentioning
confidence: 96%
“…Various candidate pathogenicity/virulence factors has been reported from the secretome of this TiK isolate such as mannitol dehydrogenase (TiMD), secretory lipase (TiL), transaldolase (TiTA), enolase (TiE), phosphoglucoseisomerase (TiPGI), thioredoxin (TiTR), peptidyl prolyl isomerase (TiPPI), and aspartate protease (TiAP) [ 64 ]. Consequently, Mishra et al [ 68 ] announced the first improved genome sequence of the monoteliosporic culture of Ti, consisting of the lowest number of 787 scaffolds with an estimated genome size of 31.83 Mbp, comprising of 9209 genes, of which 220 were virulence-associated genes (VAGs). Further, Gurjar et al [ 63 ], assembled a genome size of 33.7 Mb with a 10,113 predicted genes.…”
Section: Revelation Of Molecular Pathogenesis Mechanism By Multi- Omics Studiesmentioning
confidence: 99%